Architecture as Adventure: Concept Design for Creative Spaces - Yerianne Christa Haywood; I Gusti Ngurah Antaryama; Sri Nastiti Nugrahani Ekasiwi (Institut Teknologi Sepuluh Nopember, 2020)
The physical environment is considered as one factor which has an influence on individual’s creative capacity. While the physical setting may not directly induce one’s creativity, its effect on creativity is shown in the way it is perceived and utilized by the individual. Therefore, through subjective experience, the built environment may actively hinder or encourage one’s creative capacity. Thus, the design of creative spaces is one of architectural interest to potentially aid creative activities by focusing on the users experience of the physical setting. This paper aims to compose a design concept and criteria to address the needs of creative spaces. The literature review examines perception and experience of the built environment, sensory considerations and creativity. Therefore, a phenomenological study is used to investigate individual’s perception and subjective experience of the physical environment during the creative process. The result of this study shows that considering individuals’ needs, the design criteria is centered on movement, sensory information and social engagement. The concept derived is based on architecture as ‘adventure’, since it communicates an experience analogous to the creative process. Features of the concept are then applied to massing and form, social engagement, the natural environment and movement as an eventful experience.